Efek Kepemimpinan dan Komitmen Asosiasi terhadap Kinerja Pengawai Dinas Pendapatan Daerah Kota Sorong - Philipus Sinay; Edward Clan; Yohanes Tamunete (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the effects of leadership and organizational commitment on employee performance at the Regional Personnel Agency of Sorong City. The method applied is quantitative descriptive analysis. Based on the findings of the t-test, the tak terikatt variables have a positive and significant partial effect on the terikatt variable, with a t-value for the leadership variable of 4.1082 > t-table 1.6772, and a significance value of 0.000 < 0.05. In other words, since the t-value > t-table, the hypothesis (H1) is confirmed. The t-value for the organizational commitment variable is 6.429 > t-table 1.6772, with a significance level of 0.000 < 0.05. This indicates that t-value > t-table, and the hypothesis (H2) is also confirmed. The results of the F-test indicate an F-value of 47.824 with a significance of 0.000, which is significant < 0.05, suggesting that leadership and organizational commitment together have an effect on employee performance.